Analysis of Runoff due to The Change in Land Use at The Watershed of Upstream Ciliwung - Dwi Indriastuti (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Climate change has triggered extreme climate such as rising temperature, high rainfall intensity, rising sea water level, drought, and others (Thuc, 2014). Challenges of sustainable development are increases in various disasters, climate change and global crisis such as land use change, soil quality degradation, limited water and mineral, environmental pollution, and decreasing in biodiversity. The cause of flooding in Jakarta is due to the overflow of Ciliwung River. The changes of land use greatly affect Ciliwung River flow. Land degradation in upstream of Ciliwung watershed (Puncak area) has triggered new problem, annual flooding, especially in downstream area. The change of surface which cannot accommodate water, increasing runoff, moreover, the change of land condition which easily saturated, greatly affected the runoff conditions in Ciliwung watershed. This research using HEC-HMS software in order to know how the land uses changes and rainfall intensity affected the runoff. By using land use maps in 2000, 2005, 2010, and rainfall data in 5 (five) rainfall station near location from 1996 to 2013, it can be known how the runoff changes. Parameter calibration is done with measured discharge in Katulampa weir for each occurrence. The parameter value used in simulation later is the real value approach. Simulation by HEC HMS using CN of Spatial Planning in Ciliwung upstream area and rainfall 25 years return period gives that the highest discharge is 226.25 m3/second and water level reaches to 317 cm. If included into the alert in Katulampa weir, then the condition faces to Alert 1 for during ±6 hours.